2018
DOI: 10.1088/1361-6579/aabbc2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of probabilistic classifiers for sleep stage classification

Abstract: The results suggest that CRFt is not only better at learning and predicting more complex and irregular sleep architectures, but that it also performs reasonably well in five-class classification-the standard for sleep scoring used in clinical PSG. Additionally, and albeit with a decrease in performance when compared with healthy participants, sleep stage classification in OSA patients using cardiorespiratory features and CRFt seems feasible with reasonable accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…This leads to the development of automatic sleep stage classification. Unfortunately, conventional algorithms utilizing heart rate features did not have a high accuracy for five-stage sleep stage classification [ 28 , 29 , 30 ]. Some studies tried combine sleep stages to simplify the problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to the development of automatic sleep stage classification. Unfortunately, conventional algorithms utilizing heart rate features did not have a high accuracy for five-stage sleep stage classification [ 28 , 29 , 30 ]. Some studies tried combine sleep stages to simplify the problem.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Wei et al [ 28 ] and Radha et al [ 29 ] proposed a deep learning approach for sleep stage classification, utilizing heart rate features. The authors of [ 30 ] compare different machine learning models utilizing ECG features. Studies tend to group some sleep stages together to reduce the problems, yet still fail to produce accurate classifications.…”
Section: Introductionmentioning
confidence: 99%
“…To find the unlabeled training instances that correspond to potential transitions between sleep stages, we propose to use HMMs that are popular in EEG and PSG signals processing [16]. Recently, HMMs were used in different manners for sleep EEG artefact detection [17], sleep stage classification [18] or post-hoc refinement of classification results [19].…”
Section: Active Learning and Ambiguous Instancesmentioning
confidence: 99%
“…Fonseca et al . () found that considering a time variable in addition to heart rate signals could detect sleep stages better than heart‐rate signals alone. Specifically, time and heart rate variables were discretised using K ‐means clustering, which were then used as observation sequences in HMMs and conditional random fields.…”
Section: Introductionmentioning
confidence: 99%